Generalizing Amdahl's Law for Power and Energy. - Cameron, Kirk W.; Ge, Rong (Computer (00189162), 2012)
Extending Amdahl's law to identify optimal power-performance configurations requires considering the interactive effects of power, performance, and parallel overhead.